Electron Transfer At Semiconductor / Liquid Interfaces - Al-Agealy, H.J.M.; AL-Obaidi, R.I.N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Electron Transfer reaction rate constants at Semiconductor / Liquid interfaces are calculated dy using the Fermi Golden Rule for Semiconductor. The reorganization energy ï€¨ ï€© eVï„ is computed for Semiconductor / Liquid Interfaces system in two solvents and compared with experimental value. The driving force (free energy) Î”Go(eV) is calculated depending on spectrum Ru(H2L`)2 (NCS)2 . The transfer is treated according with weak coupling (nonadiabatic) for two â€“ state level between the Semiconductor and acceptor molecule state.